2016
DOI: 10.1186/s12872-016-0409-x
|View full text |Cite
|
Sign up to set email alerts
|

Brachial-ankle pulse wave velocity and metabolic syndrome in general population: the APAC study

Abstract: BackgroundMetabolic syndrome (MetS) is correlated with arterial stiffness and can be evaluated by brachial-ankle pulse wave velocity (baPWV). We investigated potential associations between MetS and baPWV in a Chinese community population.MethodsThe community-based Asymptomatic Polyvascular Abnormalities in Community study examined asymptomatic polyvascular abnormalities in a Chinese population aged ≥40 years. The relationship between MetS and its components and baPWV was analyzed by multivariate logistic and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…Concerning the impact of other CV risk factors on PWV, literature is currently inconsistent. Besides age and blood pressure, BMI, central obesity, triglycerides (TG), high-density lipoprotein cholesterol (HDL), fasting plasma glucose (FPG) and uric acid (UA) were reported to be associated with baPWV [ 23 , 26 28 , 31 ]. We could confirm these significant associations in our cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the impact of other CV risk factors on PWV, literature is currently inconsistent. Besides age and blood pressure, BMI, central obesity, triglycerides (TG), high-density lipoprotein cholesterol (HDL), fasting plasma glucose (FPG) and uric acid (UA) were reported to be associated with baPWV [ 23 , 26 28 , 31 ]. We could confirm these significant associations in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies demonstrated that age and hypertension [ 14 , 23 , 24 ] strongly influence PWV, the impact of other conventional atherosclerotic risk factors, such as diabetes mellitus [ 25 ], metabolic syndrome [ 26 28 ], and smoking [ 29 , 30 ] is inconsistent. Reference values based on a large-scale European population have only been established for the gold standard cfPWV by one multi-centre study [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with MetS have twofold risk of presenting stiff arteries when compared to individuals without MetS, even after controlling for age, sex and occurrence of diabetes mellitus [ 14 ]. Arterial stiffness of central arterial segments is normally identified before clinical manifestations of cardiovascular disease [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pulse wave velocity (PWV) is a method of measuring arterial stiffness that indirectly presents as a surrogate marker for CVD risk and is closely correlated with the parameters of metabolic syndrome [ 22 , 23 ]. Carotid-femoral PWV (cfPWV) is considered the gold-standard measurement for arterial stiffness [ 24 ].…”
Section: Discussionmentioning
confidence: 99%